Regeneration of Adventitious Shoots from Induced Callus of Lantana Camara L. Plant by in Vitro Culture Technique - Ibrahim, Majid A.; Sabti, Manal Z.; Mussa, Shiamaa H. (Jordan Journal of Agricultural Sciences, 2020)
The results showed that the MS medium supplemented with a concentration of 1.4 mg L-1 of NAA and 0.1 mg L-1 BA resulted in the highest significant value in the percentage of response to callus induction of 96.67% compared with the other combinations of growth regulators. The results showed that a combination of 9.5 mg L-1 BA and 0.2 mg L-1 NAA which was added to the MS medium recorded the highest percentage of response to indirect adventitious shoot formation from callus of Lantana Camara, several shoots per 100 mg callus and shoot length reached 96.67%, 10 shoots per 100 mg callus and 3.00 cm, respectively, after 12 weeks of culturing. The adventitious shoots of indirect organogenesis of Lantana Camara were rooted when cultured on the MS medium supplemented with a concentration of 1.0 mg L-1 of NAA and 0.1 mg L-1 BA after 8 weeks of planting.